Egyptian temples in Lower Nubia, New Kingdom (1580-1085 BC): Historical-archaeological study - AL-Khaleeli, Dr.Bushra (Al-Adab Journal, 2021)
The concept of the temple in the ancient Egyptian faith was derived from the ancient Egyptian philosophical theological thought; Believing that the gods live like human society governed by laws and customs; And they organize their lives by forming a family and living in their own dwellings in the sky, and from here doubts began to appear in the minds of the ancient Egyptian since his association with the gods, which is how the gods could respond to him while they were far from him and inhabiting the sky? These doubts prompted the ancient Egyptian to propose solutions to bring him closer to the gods? He found that his construction of temples to the gods throughout the country and abroad are possible solutions for offering sacrifices, holding rituals and religious holidays, and closely offering obedience and loyalty to the gods. Accordingly, this study seeks a historical-archaeological research on Egyptian temples in Lower Nubia, and in this context, it is necessary to follow the systematic cognitive sequence of the ancient Egyptian mentality in spreading his religious beliefs outside the borders of his country, as well as knowing the setting of his carefully studied goals about the areas he chose to build. Temples in it; He chose Lower Nubia as a result of its possession of rich resources, including gold and incense, the two materials that were included in the ancient Egyptian religious rituals, in addition to following the strategic marketing plan that the ancient Egyptian pursued in building his commercial centers near the temples he built in Lower Nubia in order to facilitate the task of Sell ​​his marketing products.